Reward Practices and Performance from Islamic Perspective: Aligning Motivation and Responsibility - Usman, Muliati; Harmen, Hamdi (Journal of Technology Management and Business, 2021)
Rewards will provide a positive effect for enhancing the performance of workers. However, there are crucial factors that influence the practice of reward on performance which is motivation and responsibility. These two factors will strengthen or weaken reward practices on organisational performance. Indeed, for Muslim workers, carrying out Islamic values at work is an obligation. A Muslim living in the world is according to the principles set out in Islam. They must remain guided by Islamic values in carrying out their work obligations, including for the issue of reward. Therefore, this study intends to provide further insight by analyzing the concept of reward practices on performance from an Islamic point of view through key elements that emphasise the need for responsibility and motivation of Muslim workers. This study identified that reward had a negative impact on the psychological of workers when it cannot provide justice for the worker. They perceived that the effort is given to the organisation and what workers get from the organization does not match. Therefore, organizations have to apply the best reward management system to anticipate this issue. It should be noted, however, that Islam requires a Muslim worker to build self-motivation for work as work is an act of worship to Allah. Thus, work is not only to fulfill material needs but a  responsibility to Allah S.W.T. Thus, organisational reward needs to implement Islamic values by aligning motivation and responsibility of Muslim workers. Only then, organisation can develop an awareness of the workers on the importance of Islamic values at work through a comprehensive Islamic program in order to enhance their motivation and responsibility.